HUBUNGAN GOOD CORPORATE GOVERNANCE (GCG) DENGAN PENGUNGKAPAN LAPORAN KEUANGAN - Danri Toni Siboro (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2007)
Due to the checs, crisis which happen in a bussines lately, relaizes the steak holders to run the bussines more sporty, transparant, honest, accountable in management and trust in managing the organization, institution, wealth or other resources to reach the goals. To reach these goals, many theorities and policy appear such as the management system and another concept such as good corporate governance (GCG) concept.One of the good corporate governance (GCG) principle forms is to open the public information access based on the transparancy corridor and information transparancy. One of those informations is the accounting report. The accounting report which is made must have significance meaning, or  there isn’t any hidden information or disclosure.